Análise de propagação de trincas por meio da mecânica da fratura - Marcelo Lopes Martins Borges (2010)
The aim of this work is to study a methodology based on the application of the Fracture Mechanics fundamentals to analyze the crack propagation in mechanical components subjected to fatigue in order to estimate the time, or the number of cycles, that these elements will endurance when subjected to cyclic or variable loading. The methodology was divided into two stages: the first corresponds to the global linear elastic analysis of the structure without the presence of cracks, based on the finite element method (FEM) or on boundary element method (BEM); on the second stage a crack is introduced in the structure and its propagation is carried out using BEM. Three cases are presented. In the first one, it was considered the crack propagation in a plate under remote tension, and the results were compared to values available in Fracture Mechanics manuals. The second case referred to an austempered nodular ductile iron compact test specimen in tension. The results were compared to those obtained experimentally by DIAS (2006) in his Ph.D. thesis. In the last case an analysis of a mandrel shaft that fractured after almost twelve years in service was conducted, considering a cyclic load of constant amplitude. The results were compared with the life estimated by the Miners linear rule of cumulative damage. The methodology presented and tested in this work was feasible for predicting crack propagation in structural elements.